Serpins and serpinopathies - Whisstock, James (Henry Stewart Talks, 2007)
Serpins, Proteases, Serpin function, Serpin structure, Serpin protease interactions, Role of co-factors in serpin function, Serpin polymerization and dysfunction, Antitrypsin deficiency, Z-antitrypsin, Mechanism of serpin polymerization, Other serpin deficiencies, Antithrombin deficiency, Neuroserpin polymerization, Antichymotrypsin deficiency, Approaches to combat serpinopathies
Archived at 2020/08/13